Microstructure correlation between eutectic and bulk metallic glass interpreted via dual-cluster formulas model. Issue 6 (19th March 2022) - Chen, Jixiang; Xu, Xiangtian; Sha, Xiaosong; Zhao, Jiale; Cheng, Yi
ABSTRACT: It has been widely accepted that bulk metallic glasses (BMGs) are usually near deep eutectic compositions. However, the microstructure relationship between eutectic and BMG is still unresolved. The present work is devoted to revealing the atomic short-range-order microstructure similarity of eutectic and BMG. Principal cluster is defined according to atomic close-packing and degree of isolation and then dual-cluster formulas model [(principal cluster)1 + (principal cluster)2 ](glue atom)2, 4 or 6 is developed to interpret the eutectic and BMG composition, where the two principal clusters are derived from the eutectic-related phases. As a verification, deep eutectic and corresponding BMGs of Cu–Zr binary system are analysed. The study demonstrates that short-range-order microstructure correlation between eutectic and eutectic-type BMG is reflected by eutectic-related principal cluster. Meanwhile, a detailed procedure of design BMGs is established.